2015
DOI: 10.1002/jor.23083
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products induced VEGF production and inflammatory responses in human synoviocytes via RAGE-NF-κB pathway activation

Abstract: Aging and diabetes are known to be the major cause to affect the progression of osteoarthritis (OA). Advanced glycation end products (AGEs) have been observed to accumulate in various organs especially in joint tissue and do damage to the joint tissue during aging and diabetes. Synovial angiogenesis and inflammation are observed across the full range of OA severity. The signaling pathway of AGEs on vascular endothelial growth factor (VEGF) production and inflammatory responses in synoviocytes are still unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…AGE may deregulate CSF‐1 expression via three ways: extracellular AGE‐Ager signaling, intracellular O‐GlcNAc modification by OGT/OGA, and modifications of transcription factors by intracellularly formed AGE binding . In this study, we observed that high glucose downregulated OGT levels.…”
Section: Discussionmentioning
confidence: 48%
“…AGE may deregulate CSF‐1 expression via three ways: extracellular AGE‐Ager signaling, intracellular O‐GlcNAc modification by OGT/OGA, and modifications of transcription factors by intracellularly formed AGE binding . In this study, we observed that high glucose downregulated OGT levels.…”
Section: Discussionmentioning
confidence: 48%
“…Matrix metalloproteinase-13 (MMP-13) was shown to be one of the major catabolic factors for IVDD (10)(11)(12). Studies demonstrated that MMP-13 was activated under diabetic conditions (13)(14)(15); however, how MMP-13 is regulated in diabetic IVDD remains elusive.…”
mentioning
confidence: 99%
“…The activation of the AGE‐RAGE axis seems to be involved in the VEGF‐mediated synovial neoangiogenesis as well, as the administration of AGEs in vitro induced a dose‐dependent expression of VEGF, IL‐6, COX‐2, PGE 2 , and MMP‐13 via the NF‐κB in human synoviocytes . Indeed, an animal study involving a mouse model of intraarticular fracture and subsequent post‐traumatic OA showed a marked grade of synovitis and cartilage degradation due to RAGE activation, while knockout animals for the RAGE gene demonstrated a faster recovery from synovial inflammation and bone fracture, thus not leading to a frank OA …”
Section: The Role Of Advanced Glycation End‐productsmentioning
confidence: 99%
“…Indeed, metylglyoxal (MG) and free metylglyoxal-derived hydroimidazolone (MG-H1) levels in the F I G U R E 1 Hypothetical model depicting the role of hyperglycaemia in the development of OA synovial fluid were reported to be significantly correlated with OA, while levels of phosphatidylcholine acyl-alkyl (PC) C34:3 and C36:3, which have protective properties against AGE-mediated oxidative stress, were lower 52. The activation of the AGE-RAGE axis seems to be involved in the VEGF-mediated synovial neoangiogenesis as well, as the administration of AGEs in vitro induced a dose-dependent expression of VEGF, IL-6, COX-2, PGE 2 , and MMP-13 via the NF-κB in human synoviocytes 66. Indeed, an animal study involving a mouse model of intraarticular fracture and subsequent post-traumatic OA showed a marked grade of synovitis and cartilage degradation due to RAGE activation, while knockout animals for the RAGE gene demonstrated a faster recovery from synovial inflammation and bone fracture, thus not leading to a frank OA 67.…”
mentioning
confidence: 92%